2012
DOI: 10.1002/jmv.23289
|View full text |Cite
|
Sign up to set email alerts
|

Study of CD4+CD8+ Double positive T‐lymphocyte phenotype and function in Indian patients infected with HIV‐1

Abstract: CD4+CD8+ double positive T cells represent a minor peripheral blood lymphocyte population. CD4+ expression on CD8+ T cells is induced following cellular activation, and as chronic HIV‐1 infection is associated with generalized immune activation, double positive T cells studies have become necessary to understand the immunopathology of human immunodeficiency virus (HIV). The frequency of double positive T cells in persons infected with HIV was studied in comparison to uninfected controls. Further, the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 59 publications
(75 reference statements)
4
21
0
Order By: Relevance
“…Moreover, results showed that TCR ␥␦+ values can be obtained using the double-negative CD3+CD4−CD8− phenotype. The CD4/CD8 ratio obtained in this study was comparable with values reported by other studies [4,9,11,12,14,16,17,[20][21][22]30]. However, when gender was evaluated, some studies [11,12,17,21,22] found a higher ratio among females, while others [4,7,9,14,16,32], including this study, did not find differences between genders.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, results showed that TCR ␥␦+ values can be obtained using the double-negative CD3+CD4−CD8− phenotype. The CD4/CD8 ratio obtained in this study was comparable with values reported by other studies [4,9,11,12,14,16,17,[20][21][22]30]. However, when gender was evaluated, some studies [11,12,17,21,22] found a higher ratio among females, while others [4,7,9,14,16,32], including this study, did not find differences between genders.…”
Section: Discussionsupporting
confidence: 93%
“…Chauhan et al [30] observed that the range for their uninfected control group (n = 10) was 0.1-1.2%. However, in this study, the calculated range for healthy adults was wider, probably because a larger number of persons were evaluated.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…20 Furthermore, both cell populations behave similarly in ACPAþ RA patients, 8 and in patients with chronic infections like HIV; 17 moreover, it has been proposed that CD4þCD8þ DP T cells could originate from CD4þCD28null. 21 CD4þCD8þ DP T cells have a pro-inflammatory phenotype, including the production of pro-inflammatory cytokines like IFN-g, 8,[8][9][10][11][12][13][14][15][16][17][18][19][20][21] This subpopulation is associated with a higher level of TNF-a. 22 CD4þCD8þ DP T cells express CD56 and perforin, suggesting they have a cytotoxic capacity.…”
Section: Introductionmentioning
confidence: 99%
“…The double-positive developmental stage of T lymphocytes (CD3 + CD4 + CD8 + ) was elevated upon exposure to cell lysates of P. falciparum . This phenomenon could be associated with the severity of malaria as has been reported for several other infectious diseases, such as HIV [26] and Chagas disease [27], including autoimmune diseases [28] suggesting an immune suppressive role of this cell type [29]. On the other hand, the increment of double-negative developmental stage of T lymphocytes (CD3 + CD4 − CD8 − ) when activated with cell lysates of the P. vivax malaria parasite, emphasized the difference in the response of newly produced immune cells to the two parasites.…”
Section: Discussionmentioning
confidence: 70%